The Effect of Government Public Expenditure on Economic Growth of Arab Spring Impacted Countries - Mustafa, S. Almajdob (Universiti Malaysia Sarawak (UNIMAS), 2021)
The Arab uprisings in Tunisia, Egypt, Yemen, Libya, and Syria over the past five years represent a conundrum. Despite the previous series of economic reforms and high volumes of aid flows to governments of the Arab world during the past two decades, many Arab countries still have serious socioeconomic and developmental issues, mainly related to their government spending on its public expenditure. other scholars see that the low economic performance in the Arab region is thought to be associated with the “politically and economically captured system” in the region in which government tends to benefit specific groups on patronage network, leaving the needy out from the assistance system. Despite the increase in government public expenditure annually, the impact of these doesn’t goes hand in hand with its economic growth. This study examines the relationship between government spending (education, health and military) and economic growth in the Arab Spring Countries, which includes five member-states of the League of Arab States, using panel data of 15 years (2000-2014). Besides the study examine the short run and long run relationship of government public expenditure towards economic growth as well as assessing its relationships through quantile regression. Diagnostic test such Multi-collinearity tests, Heteroscedasticity test and Serial Correlation test are conducted to it tests implicitly whether a regression model is correctly specified in terms of the regressors that have been included. The study uses the panel OLS regression models; panel fixed effect model (FEM) regression and the panel random effect model (REM) regression and quantile regression model. The panel unit root test indicated that the results of the all variable are not significant at level (0) but significant at first difference I (1) at five percent, indicating that the variables employed may be co-integrated. The estimated panel data regression using panel OLS regression, FEM regression and REM regression indicated that the results of the estimated parameters were iv spurious having both autocorrelations and heteroscedasticity. The results revealed that fixed effect is appropriate model in the study indicating significant and positive relationship between the government expenditure on health and education towards economic growth. The effect of government expenditure (health, education and military) on economic growth GDP was found to be varied, though significantly positive through the quantile regression model. It suggested that when the economic growth is high, increasing the government spending might have a positive effect and stimulate economic growth.